An extended window of opportunity for G-CSF treatment in cerebral ischemia - Schneider, Armin (BioMed Central, 2006)
BACKGROUND: Granulocyte-colony stimulating factor (G-CSF) is known as a powerful regulator of white blood cell proliferation and differentiation in mammals. We, and others, have shown that G-CSF is effective in treating cerebral ischemia in rodents, both relating to infarct size as well as functional recovery. G-CSF and its receptor are expressed by neurons, and G-CSF regulates apoptosis and neurogenesis, providing a rational basis for its beneficial short- and long-term actions in ischemia. In addition, G-CSF may contribute to re-endothelialisation and arteriogenesis in the vasculature of the ischemic penumbra. In addition to these trophic effects, G-CSF is a potent neuroprotective factor reliably reducing infarct size in different stroke models. RESULTS: Here, we have further delayed treatment and studied effects of G-CSF on infarct volume in the middle cerebral artery occlusion (MCAO) model and functional outcome in the cortical photothrombotic model. In the MCAO model, we applied a single dose of 60 μg/kg bodyweight G-CSF in rats 4 h after onset of ischemia. Infarct volume was determined 24 h after onset of ischemia. In the rat photothrombotic model, we applied 10 μg/kg bodyweight G-CSF daily for a period of 10 days starting either 24 or 72 h after induction of ischemia. G-CSF both decreased acute infarct volume in the MCAO model, and improved recovery in the photothrombotic model at delayed timepoints. CONCLUSION: These data further strengthen G-CSF's profile as a unique candidate stroke drug, and provide an experimental basis for application of G-CSF in the post-stroke recovery phase.